Suppressive Activities of Fisetin on Particulate Matter-induced Oxidative Stress - Sim, Hyunchae; Noh, Yeeun; Choo, Samyeol; Kim, Nayeon; Lee, Taeho; Bae, Jong-Sup (Biotechnology and bioprocess engineering, 2021)
Exposure to high levels of atmospheric particulate matter (PM) with an aerodynamic diameter of less than 2.5 µm (PM 2.5 ) causes respiratory injury mainly due to oxidative stress. Although the fisetin has biological activities such as the antiviral, neuroprotective, and anti-inflammatory activities, the effect of fisetin on PM-mediated oxidative damage has not been studied. In this study, we tested the protective effect of fisetin against PM 2.5 -induced toxicity in human pulmonary artery endothelial cells (HPAECs) and its molecular mechanism. Exposure to PM 2.5 decreased cell viability in HPAECs in a time- and dose-dependent manner, possibly due to increased release of extracellular lactate dehydrogenase and generation of intracellular reactive oxygen species (ROS). Cell viability assay demonstrated that treatment of HPAECs with fisetin increased cell viability and reduced PM 2.5 -induced oxidative stress in a dose-dependent manner. Serum- and glucocorticoid-inducible kinase 1 (SGK1), a crucial cell survival factor, was downregulated by PM 2.5 which was recovered by fisetin. Furthermore, fisetin treatment inhibited intracellular ROS in HPAECs generated by PM 2.5 . Moreover, decreased antioxidant enzymes activities of superoxide dismutase and catalase level in PM 2.5 -treated cells were reversed by fisetin treatment. Our results suggest that fisetin effectively protects human HPAECs from PM 2.5 -induced oxidative damage via antioxidant effects.